PENDEKATAN KARAKTERISTIK RESPON GETARAN SISTEM 2 DOF SETELAH PENAMBAHAN INDEPENDENT DUAL TRANSLASIONAL DYNAMIC VIBRATION ABSORBER - Susastro Susastro (University of Muhammadiyah Jakarta, 2019)
Dual Translational dynamic vibration absorber (dDVA) is two DVA masses that can move in the translational direction and given into the system to reduce system-translation translational vibrations. The research about using dual translational DVA to reduce vibration with the simulation method has been done, but a study about using the experimental method in that study to do validation from the simulation results that never been done. In this research we conducted a study related to the characteristics of 2 DOF system vibration response after the addition of dual translational DVA with an experimental approach and compared the results with simulation results data. Comparison between experiment date and simulation date is done in order to determine the level of error between the two methods. Simulation data is obtained by simulating the existing equations of motion from the study of literature, while the experimental data is obtained from testing with a DVA test with several changes in the frequency of excitation. From this research shows that the vibration characteristics of the experimental results are the same as the characteristics of the vibration of the simulation results, with an average significance level of 91.5%. The error that occurs between the results of the simulation and experiment is caused by the disappearance of some vibrations from the main system to the environment around the system, so that resulting differences result between simulation and experiment.